2009
DOI: 10.1534/genetics.109.102350
|View full text |Cite
|
Sign up to set email alerts
|

Association Genetics of Coastal Douglas Fir (Pseudotsuga menziesii var. menziesii, Pinaceae). I. Cold-Hardiness Related Traits

Abstract: Adaptation to cold is one of the greatest challenges to forest trees. This process is highly synchronized with environmental cues relating to photoperiod and temperature. Here, we use a candidate gene-based approach to search for genetic associations between 384 single-nucleotide polymorphism (SNP) markers from 117 candidate genes and 21 cold-hardiness related traits. A general linear model approach, including population structure estimates as covariates, was implemented for each marker–trait pair. We discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
172
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(190 citation statements)
references
References 84 publications
(105 reference statements)
16
172
0
1
Order By: Relevance
“…The excess of negative Tajima's D, Fay and Wu's H, as well as Fu's F s values noted in this study was also observed in other temperate or boreal species being largely displaced during the Holocene, such as P. abies (Heuertz et al, 2006;Namroud et al, 2010), P. sylvestris (Pyhäjärvi et al, 2007), P. menziesii var. menziesii (Eckert et al, 2009b) and Picea mariana (Namroud et al, 2010). In other conifer species less displaced during the Holocene, the excess of negative Tajima's D values is not the rule.…”
Section: Ld and Selectionmentioning
confidence: 96%
See 1 more Smart Citation
“…The excess of negative Tajima's D, Fay and Wu's H, as well as Fu's F s values noted in this study was also observed in other temperate or boreal species being largely displaced during the Holocene, such as P. abies (Heuertz et al, 2006;Namroud et al, 2010), P. sylvestris (Pyhäjärvi et al, 2007), P. menziesii var. menziesii (Eckert et al, 2009b) and Picea mariana (Namroud et al, 2010). In other conifer species less displaced during the Holocene, the excess of negative Tajima's D values is not the rule.…”
Section: Ld and Selectionmentioning
confidence: 96%
“…Association studies involving candidate genes have been successful to detect genetic polymorphisms associated with phenotypic variation in loblolly pine (González-Martínez et al, 2008), Douglas fir (Eckert et al, 2009b), Sitka spruce (Holliday et al, 2010) and white spruce .…”
Section: Introductionmentioning
confidence: 99%
“…The set of associations in loblolly pine, therefore, is comprehensive with regard to phenotypic trait diversity. This includes both explicitly and implicitly measured phenotypic traits, as environmental associations are expected to reflect unmeasured phenotypic traits since phenotypic traits are selected upon in natural populations (see Eckert et al 2009a for an example).Loblolly pine is an ecologically and economically important tree species of southeastern North America. Its range extends from eastern Texas throughout the southeastern United States and north into Delaware and thus is distributed across diverse environmental gradients ( Figure 1).…”
mentioning
confidence: 99%
“…The set of associations in loblolly pine, therefore, is comprehensive with regard to phenotypic trait diversity. This includes both explicitly and implicitly measured phenotypic traits, as environmental associations are expected to reflect unmeasured phenotypic traits since phenotypic traits are selected upon in natural populations (see Eckert et al 2009a for an example).…”
mentioning
confidence: 99%
“…Similarly, Holliday et al (2010) found associations between 28 genes and phenotypic variance in two dormancy-related traits, autumn cold hardiness and budset timing, for Stika spruce, across its range. Eckert et al (2009) identified associations between genes and cold-hardiness related traits for coastal Douglas fir.…”
Section: Introductionmentioning
confidence: 99%